Development and Validation of Chromatographic Methods for Simultaneous Determination of Ibuprofen and Famotidine in Presence of Related Substances in Pharmaceutical Formulations - Eman S Elzanfaly; Hala E Zaazaa; Aya T Soudi; Maissa Y Salem (Acta Chimica Slovenica, 2014)
Two validated methods for the simultaneous determination of ibuprofen and famotidine in the presence of ibuprofen impurity (4-isobutylacetophenone) and or famotidine degradation products were described. The first method was a simple TLC method where separation was performed on silica gel platesusing ethyl acetate: methanol: ammonia (9:2:1, by volume) as a mobile phase. Rf values were found to be 0.40, 0.94, 0.66, 0.27, 0.83 for ibuprofen, 4-isobutylacetophenone, famotidine, famotidine acid and basic degradation products, respectively. The second method is by HPLC on C18 column using methanol: phosphate buffer pH 3 (80:20, v/v) as a mobile phase.  Retention times were found to be 2.2, 9.9, and 8.6 for famotidine, ibuprofen, and 4-isobutylacetophenone, respectively. Both methods were validated according to the ICH guidelines and applied for the determination of the two drugs in pure powder and combined dosage form without interference from the excipients.